Slip, Displacement and Stress Scenarios on the Lhoksumawe Fault to Determine the Movement and Direction of the Rupture Area - Andrean V H Simanjuntak; Herman Fithra; Azhari Azhari; Deassy Siska (Faculty of Engineering, Malikussaleh University, 2018)
Aceh Province has 23 active faults in land which very devastating and destruvtive. It makes Aceh very vulnerable to earthquake, same like in one of major cities in Aceh Province, Lhoksumawe, which has an active fault that passes through inside its territory. Lhoksumawe fault is located in the Northen part of Aceh, very close to Lhoksumawe city as the mother city in there. According to BMKG earthquake information, there was a moderate earthquake with M4.7 at June 19th 2016. The hypocenter is located in the sea and suspected by Lhoksumawe fault. So far, some reference about Lhoksumawe fault can't describe exactly this fault, whether it's down to the sea or not. We must concern and know the activity of this fault, because the fault is still active even has small slip rate just 1 mm/year, but can generate the earthquake until M 6.5. We make the seismicity map and some scenarios to calculate and analyze the slip direction, displacement and stress model. We assume the earthquake has strike-slip mechanism with right-lateral movement at 10 km depth and located in the center of this fault. With M6.5, slip until 5 m and fault dimension 40 x 15 km, we can get good model and scenarios. The results show us, if the vertical displacement has positive value until 0.5 m and horizontal until 1 m, which following the double couple pattern. For stress, we use the effective stress which very simple to knowing the stress rate, the highest value until 1 MPa. This results is very important to know how the earthquake activity with strikeslip mechanism occurred Lhoksumawe Fault, because, Lhoksumawe city has large population and highly developed economic growth, natural disasters such as earthquakes must really be a concern in this region.